2015
DOI: 10.1016/j.agee.2015.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Observed and predicted changes in soil carbon stocks under export and diversified agriculture in the Caribbean. The case study of Guadeloupe

Abstract: Export agriculture in the Caribbean is often blamed for pollution of soils and water resources. At the same time, the reduction of preferences in the international markets for major agricultural exports from the Caribbean induced a partial reorientation of the agriculture towards the local markets, which included crop diversification. This study was carried out to assess the sustainability of that agricultural switch with respect to maintaining, increasing or decreasing soil organic carbon (SOC) stocks. We ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 31 publications
1
62
0
Order By: Relevance
“…The annual temperature ranges from 20.1 and 31.9°C (France Meteorological Service, http://www.meteo.gp). This island is characterized by a humid tropical climate and a variety of soil types: ferralsols, nitisols, andosols and vertisols [20]. The mean annual rainfall in Basse-Terre is comprised between 1400 mm and 3500 mm (France Meteorological Service, http://www.meteo.gp).…”
Section: Research Areamentioning
confidence: 99%
See 2 more Smart Citations
“…The annual temperature ranges from 20.1 and 31.9°C (France Meteorological Service, http://www.meteo.gp). This island is characterized by a humid tropical climate and a variety of soil types: ferralsols, nitisols, andosols and vertisols [20]. The mean annual rainfall in Basse-Terre is comprised between 1400 mm and 3500 mm (France Meteorological Service, http://www.meteo.gp).…”
Section: Research Areamentioning
confidence: 99%
“…The mean annual rainfall in Basse-Terre is comprised between 1400 mm and 3500 mm (France Meteorological Service, http://www.meteo.gp). On the contrary, Grande-Terre (586 km 2 ) is characterized by a slightly undulating surface, and the relief rarely exceeds 40 m [20]. The climate is tropical, with a mean annual rainfall between 1300 mm and 1600 mm, and soils are mostly vertisols.…”
Section: Research Areamentioning
confidence: 99%
See 1 more Smart Citation
“…These good results explain why many smallholders are orientated toward this type of organic input and did not adopt AES old . On the contrary, the economic performance of SLUD for large farms was much lower than that of NFER, which explains why sewage sludge is not used in these farms (Sierra et al, 2015). Besides, at the landscape scale, the adoption of sewage sludge as an organic amendment is limited because of regulatory constraints.…”
Section: Parametermentioning
confidence: 99%
“…comm.). However, several farm surveys have indicated that 20% of farmers use organic amendments such as sewage sludge and manure (Sierra et al, 2015), which suggests that farmers are interested in using organic amendments but are preferentially orientated toward freely-available amendments. Therefore, in order to ensure that AES is more efficient at the landscape scale, a more detailed analysis of the performance of organic amendment strategies needs to be carried out.…”
Section: Introductionmentioning
confidence: 99%